2020
DOI: 10.34117/bjdv6n4-330
|View full text |Cite
|
Sign up to set email alerts
|

Functional and antioxidant properties of a chicken blood meal hydrolysate

Abstract: Chicken blood is a slaughterhouse by-product rich in protein commonly transformed into blood meal. In this study, the potential of chicken blood meal as a source of protein hydrolysates with interesting properties for the industry was investigated. The hydrolysis performed at 60 °C, pH 8.0 and 5% enzyme-to-substrate ratio with Alcalase® 2.4L for 90 minutes resulted in a DH of 19.3% by the pH-stat method and 22.7% by the OPA assay. A 1:3 (v/v) O/W emulsion prepared with 1% hydrolysate solution had an emulsifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Enzymatic hydrolysis allows releasing specific peptide sequences that may exert a range of biological activities. For instance, several studies have identified active fractions from red cell or plasma protein hydrolysates exerting antioxidant, antihypertensive or antimicrobial properties (Olagunju et al ., 2018; Alves et al ., 2020). Among these bioactivities, the presence of peptides exerting antioxidant activity in blood protein hydrolysates (Verma et al ., 2019) may be advantageous when considering the dietary supplementation of haem iron.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic hydrolysis allows releasing specific peptide sequences that may exert a range of biological activities. For instance, several studies have identified active fractions from red cell or plasma protein hydrolysates exerting antioxidant, antihypertensive or antimicrobial properties (Olagunju et al ., 2018; Alves et al ., 2020). Among these bioactivities, the presence of peptides exerting antioxidant activity in blood protein hydrolysates (Verma et al ., 2019) may be advantageous when considering the dietary supplementation of haem iron.…”
Section: Introductionmentioning
confidence: 99%